The role of English as a scientific metalanguage for research in pragmatics: Reflections on the metapragmatics of "politeness" in Japanese. (11th November 2015) - Haugh, Michael
Abstract : Much of the theorisation undertaken in pragmatics has afforded English a privileged place, not only as the object of analysis but also as the means through which such theoretical discussions have been accomplished. Yet as a number of researchers have pointed out, the language in which the description, analysis and theorisation of pragmatic phenomena is undertaken can have an influence on how the research object(s) in question are understood. In this paper, the role of English as our scientific metalanguage in research on "politeness" in Japanese is considered. It is argued that in order to start managing such challenges for research in pragmatics we need to go beyond the study of abstract or decontextualised meanings of words and move towards the analysis of emic concepts and emic practices. It is concluded that rather than abandoning notions such as "politeness" in favour of seemingly less culturally-imbued terms, what is needed instead is greater awareness of what the use of English as a scientific metalanguage both affords for researchers working in pragmatics, along with the challenges it can create for such work.